OWC WEC integrated within a breakwater versus isolated: Experimental and numerical theoretical study. (December 2017) - Howe, Damon; Nader, Jean-Roch
Highlights: Numerical model data validated with experimental model results. Power and volume flux compared for isolated and breakwater mounted OWC devices. System damping optimisation investigated to aid optimal power extraction. Breakwater integration increased power output compared to isolated configuration. System damping is not frequency dependent, hence uniform damping can be applied. Abstract: Oscillating Water Column (OWC) devices are one of the most promising technologies to be implemented into already existing or in-development ocean structures, such as breakwaters. All moving components to retrieve power from the waves are well above the waterline and the still structure can be easily incorporated within solid edifices. In this paper, we investigate the hydrodynamic response of two types of Bent Duct OWC devices with different inlet geometries, both in isolation and when implemented in a flat-faced breakwater. A rectangular and circular cross-sectional shaped OWC device are used for comparison. Numerical method using a FEM based frequency domain model and experimental investigation using the Australian Maritime College wave basin are applied and the results evaluated across a range of frequencies, 0.5 Hz–1.2 Hz. Both the capture width and volume flux resulting from the numerical method match accurately with those resulting from the experiment. Discrepancies only arise around the natural resonance frequency where the assumptions of small amplitudes become erroneous. The implementation of the device within the breakwater was found to significantly enhance the capture width of each device, while the variation in inlet geometry provided low deviations in the results.